Fracture Resistance of Roots after Application of Different Sealers - Dibaji, Fatemeh; Afkhami, Farzaneh; Bidkhori, Babak; Kharazifard, Mohammad Javad (Iranian Endodontic Journal, 2016)
Introduction: Vertical root fracture inevitably leads to tooth extraction. Thus, root filling with obturating materials and sealers that can reinforce the tooth would be an ideal way to reduce fracture in root treated teeth. This study aimed to assess the fracture resistance of roots following the application of different sealers including Epiphany, iRoot sealer and AH-plus. Methods and Materials: Fifty extracted human single-canal premolars without caries, curvature or cracks were used in this study. Tooth crowns were cut to yield 13-mm-long roots. Five roots were put in the negative control group and were left unprepared. Forty-five canals were prepared using ProTaper rotary files up to F3 and were then randomly divided into three groups based on the sealer type (n=15). The root canals were filled using cold lateral condensation technique with gutta-percha and AH-Plus sealer, gutta-percha and iRoot sealer and Resilon and Epiphany sealer, in groups one to three, respectively. The roots were then mounted in acrylic molds for fracture resistance testing and subjected to compressive load at a crosshead speed of 1mm/min until fracture. Data were analyzed using the one-way ANOVA. Results: The mean fracture resistance was 673.38±170.42 N in AH-Plus, 562.00±184.68 N in iRoot, 708.03±228.05 N in Resilon and 592.59±117.29 N in the control group. No statistically significant difference was found between the experimental groups and the negative control group (P=0.26). Conclusion: Application of AH-Plus, bioceramic and Resilon sealers did not change the fracture resistance of roots compared to that of unprepared root canals. Keywords: AH-Plus; Bioceramic; Epiphany; Fracture Resistance; iRoot; Resilon; Sealer